2016
DOI: 10.1007/s11150-016-9332-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breastfeeding on young adult wages: new evidence from the add health

Abstract: A growing literature in economics has examined the effect of early childhood health investments on adult human capital formation and labor market outcomes. This study is the first to examine the effect of having been breastfed as an infant on young adult earnings. Using data from the National Longitudinal Study of Adolescent Health (Add Health), ordinary least squares estimates suggest that breastfeeding is associated with a 10-12 % increase in hourly earnings. However, after ensuring common support on observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…It is possible that these sociodemographic advantages are related to both successful breastfeeding and better infant health outcomes. Indeed, several studies have found that when these demographic and socioeconomic characteristics are taken into account, the long-term benefits of breastfeeding are weak or insignificant ( Cesur et al, 2017 , Colen and Ramey, 2014 , Der et al, 2006 , Evenhouse and Reilly, 2005 , Grube et al, 2015 , Jenkins and Foster, 2013 , Jiang et al, 2011 , Kramer, 2010 ; for exceptions see Belfield & Kelly 2012 ; Rees and Sabia 2015 ; Wehby 2014 ). In other words, the nonrandom selection of mothers who successfully breastfeed confounds estimates of infant health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that these sociodemographic advantages are related to both successful breastfeeding and better infant health outcomes. Indeed, several studies have found that when these demographic and socioeconomic characteristics are taken into account, the long-term benefits of breastfeeding are weak or insignificant ( Cesur et al, 2017 , Colen and Ramey, 2014 , Der et al, 2006 , Evenhouse and Reilly, 2005 , Grube et al, 2015 , Jenkins and Foster, 2013 , Jiang et al, 2011 , Kramer, 2010 ; for exceptions see Belfield & Kelly 2012 ; Rees and Sabia 2015 ; Wehby 2014 ). In other words, the nonrandom selection of mothers who successfully breastfeed confounds estimates of infant health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies employing this strategy found that among breast and formula- feeding discordant sibling pairs, outcomes were similar for children regardless of whether they were breast or formula fed. This suggests that most physical health benefits associated with breastfeeding are likely attributable to demographic characteristics such as race and socioeconomic status, and other difficult to measure unobservable characteristics ( Cesur et al, 2017 , Colen and Ramey, 2014 , Evenhouse and Reilly, 2005 ). While studies that employ sibling fixed-effects have several advantages, they are limited to families with siblings who were fed differently, and cannot evaluate families with only one child or siblings who were fed the same way.…”
Section: Introductionmentioning
confidence: 99%
“…Die entgangenen Chancen für Frauen, die sich für ein längeres Stillen entscheiden, können mitunter erheblich sein [9]. Dies gilt umso mehr, als neuere Forschungsergebnisse darauf hindeuten, dass Stillen den Babys nicht zu besseren Einkommensperspektiven verhilft [40]. Es ist wichtig, diese negativen Auswirkungen des Stillens zu berücksichtigen.…”
Section: Mütterunclassified